The Urban Double-Crop: Can Fall Vegetables and a Warm-Season Lawn Co-Exist? - Ellen M. Bauske (MDPI AG, 2021)
A gardening methodology using double-cropped cool-season vegetables and warm-season turfgrass, thereby capitalizing on the ideal growing season for each, was developed in field trials and tested in volunteers’ landscapes. Broccoli (Brassica oleracea), lettuce (Lactuca sativa), and Swiss chard (Beta vulgaris subsp. Cicla) were planted into an established hybrid bermudagrass lawn (Cynodon dactylon (L.) Pers. × C. transvaalensis Burtt-Davy ‘Tifsport’) in September. The vegetables were planted into tilled strips, 5 cm × 10 cm holes and 10 cm × 10 cm holes in the turf. All treatments produced harvestable yield, though the yield of vegetables planted in the tilled treatments and larger holes was greater than in smaller holes. Efforts to reduce turfgrass competition with vegetables by the application of glyphosate or the use of the Veggie Lawn Pod (an easily installed plastic cover on the lawn) did not increase yield. Tilled treatments left depressions that discouraged spring turfgrass recovery. The double-crop was tested by seven volunteers on their lawns. Though lawn-planted vegetables did not produce as much yield as those planted in the volunteers’ gardens, the volunteers were enthusiastic about this methodology. The volunteers reported that lawn vegetables were more difficult to plant but not more difficult to maintain, and they were easier to harvest than vegetables in their gardens. All volunteers reported satisfactory recovery of their lawns in the spring.